CHEMICAL CONSTITUENTS OF THE FRUIT PEEL FROM WHITE FLESH CITRUS GRANDIS (L.) OSBECK - M. S. MANORENJITHA; J. ZAIRI; S.K. LING; J. MAILINA; H. NUZIAH (International Journal of Pharma and Bio Sciences, 2016)
Citrus grandis commonly known as pomelo, shaddock or limau bali belongs to the family Rutaceae. The aim of this study is to identify the phytochemical components present in white flesh C. grandis fruit peels using solvent extraction and hydro distillation methods. Identification of phytochemical compounds was conducted using the GC-MS analysis and Nuclear Magnetic Resonance (NMR) spectroscopic techniques. Hexadecanoic acid and 9,12-Octadecadienoic acid (Z,Z) are 2 major compounds elucidated from hexane and ethyl acetate fractions, respectively; while limonene was identified as a major compound in essential oil. White powder obtained during methanol extraction was confirmed as naringin using NMR spectroscopic technique.